TAMAN PENDIDIKAN AL QURAN SEBAGAI SARANA PEMBENTUKAN KARAKTER ANAK DI DESA SEMAWOT - Putri Liana; Sahri Sahri (Universitas Wahid Hasyim Semarang, 2020)
Abstract The Al-Quran Education Park (TPQ) is a means to educate and build children's character, because through the Al-Quran Education Park (TPQ) children are trained from an early age to recognize, understand, learn, and apply Islamic education as a guide to life in themselves and children's character. in the future, because in this modern era the application of Islamic education is very much needed as a character shaping Islamic and religious spirit. Semawot village is one of the villages in the Sukosewu sub-district that establishes and implements Islamic education through the Al-Quran Education Park. In an effort to be able to build children's character with Islamic character and personality from an early age, the village of Semawot continues to develop and implement Islamic education, namely through the Al-Quran Education Park (TPQ) Al Mustahal. Through TPQ Al Mustahal education in Semawot village, it is hoped that it will be able to foster children's character from an early age who uphold Islamic religious values. Basically, the Al-Quran education park (TPQ) plays an important role in improving the quality of the level of Islamic education in the community. So that they are able to develop a young generation who have good morals and have an Islamic spirit in this modern era. Keyword: The Al-Quran Education Park (TPQ), Islamic education, character, early age Abstrak Taman Pendidikan Al-Quran (TPQ) merupakan sarana untuk mendidik dan membangun karakter anak, karena melalui Taman Pendidikan Al-Quran (TPQ) anak dilatih sejak dini untuk mengenal, memahami, mempelajari, dan menerapkan pendidikan Islam sebagai pedoman hidup dalam diri dan karakter anak dimasa depan, karena dizaman modern ini penerapan pendidikan islam sangat diperlukan sebagai pembentuk karakter yang berjiwa islami dan reliji. Desa semawot merupakan salah satu desa yang ada di kecamatan sukosewu yang mendirikan dan melaksanakan pendidikan Islam melalui Taman Pendidikan Al- Quran. Dalam upaya untuk dapat membangun karakter anak yang berakhlak dan kepribadian islami sejak usia dini desa semawot terus mengembangkan dan menerapkan pendidikan islam yaitu melalui Taman pendidikan Al-Quran (TPQ) Al Mustahal. Melalui pendidikan TPQ Al Mustahal di desa semawot diharapkan mampu menumbuhkan karakter anak sejak dini yang memegang teguh nilai-nilai agama Islam. Pada dasarnya Taman pendidikan Al-Quran (TPQ) berperan penting dalam meningkatkan kualitas taraf pendidikan islam dimasyarakat. Sehingga mampu membanggun generasi muda yang berakhlakul karimah dan berjiwa islamiyah dizaman modern ini. Kata Kunci : TPQ, pendidikan islam, karakter, usia dini